Foreign Ownership, Return Volatility, Trading Volume, and Risk of Stocks in Indonesia - Naufa, Ahmad Maulin; Lantara, I Wayan Nuka (UUM Press, 2017)
This study examines the relationship between foreign ownership and return volatility, trading volume, and risk of stocks at the Indonesia Stock Exchange (IDX). Panel data of selected companies listed on the LQ45 index of the IDX was employed for the period between 2011 and 2017. Foreign ownership was found to positively affect stock return volatility, trading volume, and risk. Hence, more substantial foreign ownership of stocks meant more drawbacks to Indonesian stocks. Therefore, there is a need for the Indonesian government to limit and regulate foreign shareholders in Indonesia.